Measuring the impact of an educational intervention in rheumatoid arthritis: An open-label, randomized trial - Geneviève Boily,; Paul R Fortin,; Anne-Laure Chetaille,; Louis Bessette,; Isabelle Fortin,; Jean-Luc Tremblay,; Judith Trudeau,; Alena Ikic,; Rebecca Lui,; Laëtitia Michou,; Suzanne Côté,; Johanne Tardif,; et al. (Archives of Rheumatology, 2022)
Objectives: This study aims to determine whether patients with active rheumatoid arthritis (RA), either starting on or changing biological or targeted synthetic disease-modifying antirheumatic drugs (DMARDs), demonstrate better self-management safety skills three months after receiving a multidisciplinary educational intervention compared to patients receiving usual care. Patients and methods: Between October 2015 and October 2018 , this open-label, randomized-controlled trial included a total of 107 RA patients (27 males, 80 females; mean age: 60.2±10.4 years; range, 54 to 71 years) who were on treatment or in whom treatment was changed with a biological or targeted synthetic DMARD. The patients were randomized into two groups: Group 1 (n=57) received additional intervention with educational DVD and one teleconference session and Group 2 (n=55) received usual care and were offered the intervention at three months. All patients underwent a final visit at six months. At each visit, the patients completed the BioSecure questionnaire measuring the self-care safety skills, a behavioral intention questionnaire, and the Beliefs about Medicines Questionnaire (BMQ). Results: No significant difference was observed in the Biosecure score at three months between the two groups (p=0.08). After pooling the first three-month data in Group 1 and the last three-month data in Group 2, the mean score of the BioSecure questionnaire increased to 7.10±0.92 in the group receiving educational intervention (p<0.0001). This increase was maintained at six months in Group 2 (p=0.88). The rate of appropriate behavioral intention increased over time (76% at baseline and 85% at six months for both groups). There was no significant change in the BMQ (p=0.44 to 0.84). Conclusion: The development of an educational DVD followed by a teleconference seem to improve self-care safety skills of the patients in practical situations.